1999
DOI: 10.1046/j.1365-2672.1999.00650.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of a modified Robbins device to directly compare the adhesion ofStaphylococcus epidermidisRP62A to surfaces

Abstract: C .J . L I NT ON , A. SH E RR IF F AN D M . R. MI L LA R. 1999.Staphylococcus epidermidis is a frequent cause of infection associated with the use of biomedical devices. Flow cell studies of the interaction between bacteria and surfaces do not generally allow direct comparison of different materials using the same bacterial suspension. The use of a modified Robbins Device (MRD) to compare the adhesion to different surfaces of Staph. epidermidis RP62A grown in continuous culture was investigated. Adhesion to gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…The used biofilm model with incubation times of 48 h at 37°C and early replacement of medium showed optimal results for stable and standardized biofilms in previous experiments. The used test microorganisms Pseudomonas aeruginosa SG81 and Staphylococcus epidermidis RP62A are often used for biofilm analyses and tests [40], [41], [42], [43], [44]. They are relevant biofilm forming pathogens in chronic wounds or device related infections [29], [45].…”
Section: Discussionmentioning
confidence: 99%
“…The used biofilm model with incubation times of 48 h at 37°C and early replacement of medium showed optimal results for stable and standardized biofilms in previous experiments. The used test microorganisms Pseudomonas aeruginosa SG81 and Staphylococcus epidermidis RP62A are often used for biofilm analyses and tests [40], [41], [42], [43], [44]. They are relevant biofilm forming pathogens in chronic wounds or device related infections [29], [45].…”
Section: Discussionmentioning
confidence: 99%
“…and strain 35984 (RP62A) was obtained from the American Type Culture Collection. Both were clinical isolates, produce bio®lm, and have been well characterized [3, 15,18,20,21,22,26,35]. Bacterial stock cultures were maintained on tryptic soy agar (TSA; Difco, Becton Dickinson and Co., Sparks, Md.)…”
Section: Methodsmentioning
confidence: 99%
“…However, a study evaluating the effect of shear stress on the adhesion of Staphylococcus epidermidis to a variety of materials including glass, siliconized glass, plasma-conditioned glass, titanium, stainless steel, and Teflon suggested that shear stresses ranging from 0.2 to 1.0 pN m Ϫ2 had little effect on the detachment rate of the surface-colonizing bacteria (32). Thus, the shear stress of 0.004 pN m Ϫ2 calculated for cells of S91 attached to surfaces exposed to flowing seawater in the present study likely represents a negligible force for these bacteria.…”
Section: Discussionmentioning
confidence: 99%